Nanoesferas magnéticas: estudo do sistema maghemita/sílica - Caiado, Kely Lopes (2014)
In this work, we synthesized core/shell magnetic composite type consisting of maghemite nanoparticles covered with a coating layer of amino-functionalized silica. The experimental procedure was based on four steps: i) synthesis of magnetite nanoparticles and subsequent oxidation to maghemite, ii) preparation of aqueous colloidal dispersions (ferrofluids), from maghemite nanoparticles with modal diameter of 8.4 nm or 7.2 nm functionalized with citrate ion, iii) preparation of silica magnetic nanospheres (NMS) by the modified Stöber method using different amounts of ferrofluids and tetraethoxysilane (TEOS), and iv) functionalization of silica nanospheres with amino groups using aminopropyltrimethoxysilane (APTS). Sample characteristics of NMS were determined from the iron content measurements, from high-resolution transmission electron microscopy (HRTEM) and from vibrating sample magnetometry (VSM) and they were evaluated on the basis of the synthetic parameters employed, these being the content of magnetic material (nFe/nTEOS = 0.05, nFe/nTEOS = 0.01 e nFe/nTEOS = 0.002) and the type of used ferrofluid; a freshly prepared ferrofluid or an aged ferrofluid. The study of ferrofluids by static magnetic birefringence (SMB) showed that both had aggregates of magnetic nanoparticles, although higher for the aged ferrofluid. Samples of NMS were heterogeneous, showing fractions with different amounts of magnetic material embedded. Samples obtained from the aged ferrofluid, especially those prepared from smaller ferrofluid volumes (nFe/nTEOS = 0.01 e nFe/nTEOS = 0.002), showed the presence of magnetic silica particles and "empty" silica particles, that is, free from magnetic nanoparticles. This fact was attributed to xxvii the greater degree of maghemite nanoparticles aggregation in aged ferrofluid and therefore to fewer available magnetic cores in the reaction environment for the deposition of silica by heterogeneous nucleation mechanism. The NMS particles sizes ranged from 140 to 700 nm, and most particles were larger than the expected average size (150 nm), according to the molar ratio of reagents used in the Stöber synthesis. The presence of silica particles with spherical morphology was also observed, as well as coalesced silica particles. These morphological characteristics were attributed to the size and to the arrangement of magnetic nanoparticles in the cores (compact or dispersed), which were present in the reaction mixtures. After coating with silica, nanoparticles of maghemite remained superparamagnetic at room temperature, although there was a reduction in the value of saturation magnetization. The saturation magnetization value of maghemite within the ferrofluids was 62.1 or 68.7 emug-1, whereas saturation magnetization values of maghemite within the NMS ranged between 9.5 and 37 emug-1. Nanostructured magnetic materials obtained in this work, especially the NMS prepared from the higher ratio Fe/TEOS, have greater potential of use as magnetic beads due to higher values of saturation magnetization and the possibility of being quickly attracted by the magnetic field of a permanent magnet.